Pengaruh Terpaan Berita Tentang Kebocoran Data Pengguna Tokopedia dan Aktivitas Word of Mouth Terhadap Tingkat Kepercayaan Dalam Menggunakan Tokopedia - Thriyani Rahmania; Tandiyo Pradekso; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The rise of online buying and selling activities has led to an increase in complaints about losses in transacting in e-commerce. One of them is the user data leak that occurred at Tokopedia. A number of online media reports explaining the case have become increasingly widespread and become public discussion. Assessment that comes from word of mouth tends to affect the level of someone’s trust in something. This study aims to determine the effect of news exposure about Tokopedia user data leakage and word of mouth activity on the level of trust in using Tokopedia. The theory used in this research is New Media Theory and Buyer Information Environment Theory. Tests are carried out by using the Simple Linear Regression Test with non-probability sampling techniques. This study used a sample of 60 Tokopedia Users aged 17-35 years who had seen, read, and heard news about Tokopedia user data leaks in 2020. The results showed news exposure about Tokopedia user data leakage (X1) on the level of trust in using Tokopedia (Y) obtained a significance value of 0.000 which means very significant with an influence level of 48.7%. Furthermore, word of mouth activity (X2) on the level of trust in using Tokopedia (Y) obtained a significance value of 0.268 which means that the regression test results are not significant.